Lignocellulosic Biomass into Mass-Producible Fuels A Critical Review of Hydrothermal Liquefaction and Upgrading Strategies - Adekoyejo Adeniyi Kujore; Kelechi Angelina Iheonye (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Hydrothermal liquefaction (HTL) of lignocellulosic biomass provides a viable route for converting wet, low-value residues into energy-dense biocrude suitable for upgrading to drop-in fuels. This review systematically covers feedstock selection and pretreatment strategies, fundamental HTL reaction pathways, and the effects of operating conditions and reactor configurations on product yields and distribution. Advances in biocrude characterization using chromatographic and spectroscopic techniques are reviewed alongside upgrading approaches, including solvent extraction, fractional distillation, catalytic hydrotreatment, and refinery co-processing. The generation, composition, and management of the aqueous phase are also examined, with emphasis on treatment challenges, environmental impacts, and potential valorization routes. Key technological barriers, including heteroatom removal, catalyst deactivation, integration of upgrading processes, and scale-up economics are critically assessed using insights from recent techno-economic and life cycle assessment studies. Based on literature reported between 2015 and 2026, this review identifies research priorities required to advance lignocellulosic HTL toward scalable, commercially viable, and sustainable fuel production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).